Changing the Rules? RDA and cataloguing in Europe - Danskin, Alan; Gryspeerdt, Katharine (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
This paper provides an overview of plans to implement RDA: Resource Description & Access in Europe to replace existing cataloguing rules.  It is based on survey information gathered by EURIG and CILIP CIG.  It includes background on the development of RDA as a replacement for AACR2.